Food preference of oryzaephilus surinamensis (coleoptera: silvanidae) to different types of plant products - Abdul, Nurul Huda; Mohamed, Noor Amni (SCIENDO, 2019)
Oryzaephilus surinamensis is one of the stored product insect that commonly found in Malaysia. The biological study through host range or food preferences of O. surinamensis is important for the development of sustainable management practice to control its infestation. The objective of this study was to identify the food preference of O. surinamensis to different plant products in relation to food type and moisture content. Twenty adult of O. surinamensis were exposed to three different group of food; dried fruits (date, raisin, apricot, fig), grain/cereals (rice, barley, oat grout, dried maize), and nuts (almond, ground nut, walnut, cashew nut) for 240h in laboratory Kulliyyah of Science, IIUM Kuantan. Moisture content in each food was also measured. It was found out that the most preferred food by O. surinamensis is oat groat of cereal grain group with medium level of moisture content. Further analysis on food moisture suggested that under current experimental conditions (temperature of 27℃ and 64% relative humidity within 240h of exposure), food moisture content does not affect pest infestation and distribution.